Respuesta :
f(x)= 3x + 1
f(x)= 3(3) + 1
= 9 + 1
= 10
g(x)= 4x - 5
= 4(3) - 5
= 12 - 5
= 7
So... A. f(x) is greater when x=3
f(x)= 3(3) + 1
= 9 + 1
= 10
g(x)= 4x - 5
= 4(3) - 5
= 12 - 5
= 7
So... A. f(x) is greater when x=3
Answer:
A) f(x) is greater.
Step-by-step explanation:
The given function is
[tex]f(x)=3x+1[/tex]
The function [tex]g(x)[/tex] is defined as [tex]g(x)=4x-5[/tex].
Let's evaluate each function for [tex]x=3[/tex]
[tex]f(3)=3(3)+1=9+1=10\\g(3)=4(3)-5=12-5=7[/tex]
We know that [tex]10>7[/tex].
Therefore, the function [tex]f(x)[/tex] is greater then [tex]g(x)[/tex] when [tex]x=3[/tex].
So, the right answer is A.